Effects of Mucus Visco-elasticity, Cilia Beating and Porosity Parameter on Mucus Transport in Human Lung Airways - et. al., Vikash Rana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, a two-layer circular steady state mathematical model is presented to study the mucus transport in the human lung airways by taking into account the effects of cilia beating as well as porosity parameter incorporated due to certain immotile cilia forming porous matrix bed in the serous sub-layer in contact with the epithelium. The effect of shear stress due to air motion at the mucus-air interface is also taken in the model. The serous layer fluid is considered as incompressible Newtonian fluid while mucus layer is considered as a visco-elastic fluid. The serous layer fluid is divided into twosub-layers, one in contact with the epithelium and the other in contact with themucus